Pacem in Terris: Are Papal Visits Good News for Human Rights? - Marek Endrich; Jerg Gutmann (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze the effect of state visits by the Catholic pope on human rights in the host country to understand how a small theocracy like the Vatican can exert disproportionate political influence in international politics. Our theoretical model of the strategic interaction between the Catholic Church and host governments shows how the pope's use of conditional approval and criticism incentivizes governments to refrain from human rights violations. Drawing on a new dataset of papal state visits outside Italy and a novel identification strategy, we test for the first time whether governments react by improving human rights protection in anticipation of a papal visit. Our empirical analysis offers robust evidence in support of this causal effect.
Keywords: D74; D78; F50; K38; P16; P26; P48; Z12; 330; Catholic Church; human rights; international political economy; pope; repression; rewards; sanctions